Enhanced immunity: the gut microbiota changes in high-altitude Tibetan pigs compared to Yorkshire pigs - Liu, Chengming; Dan, Haifeng; Yang, Yiting; Du, Yong; Hao, Ziling; Chen, Lei; Zhu, Kangping; Liu, Bin; Niu, Lili; Zhao, Ye; Wang, Yan; Shen, Linyuan; et al. (Frontiers in Microbiology, 2024)
IntroductionLong-term domestication in high-altitude environments has led to unique changes in the gut microbiota of Tibetan Pigs. This study aims to investigate specific alterations in the intestinal flora of Tibetan Pigs compared to Yorkshire pigs.MethodsWe employed 16S rRNA and metagenomic sequencing technologies for comprehensive analysis of the gut microbiota. The data collected allowed us to assess microbial community structures and functional capabilities.ResultsOur analysis revealed that Tibetan Pigs raised under a “free-range + supplementary feeding” model exhibited increased abundance of microbial communities associated with short-chain fatty acid synthesis and the digestion of cellulose and hemicellulose. Notably, the characteristic bacterium Rhodococcus, commonly found in high-altitude environments, was enriched in the gut microbiota of Tibetan Pigs, facilitating the efficient utilization of natural compounds and degradation of toxic substances. Additionally, the increased abundance of probiotics in these pigs enhances their immunity, which may involve mechanisms such as disrupting the structure of pathogenic bacteria and detoxifying harmful metabolites.DiscussionThese findings underscore the advantages of Tibetan Pigs over common commercial breeds, highlighting their unique gut microbiota adaptations. Furthermore, they open new avenues for screening potential probiotics and developing genetic breeding strategies for improved livestock varieties.ConclusionUnderstanding the distinct gut microbiota of Tibetan Pigs provides valuable insights into their health benefits and resilience, contributing to future research on breed improvement and microbiome applications in agriculture.